Principles of Information Systems, 14th Edition - Ralph Stair; George Reynolds (Cengage Learning, 2020)
Equip students with an understanding of core information systems (IS) principles and how these principles apply to today's business with Stair/Reynolds' PRINCIPLES OF INFORMATION SYSTEMS, 14E. This completely reorganized edition follows a backward design approach to ensure all content and assessments align to clear, measurable learning objectives. Students discover how IS can increase profits and reduce costs as they explore the latest developments in big data, business intelligence, cloud computing, cybercrime, e-commerce, enterprise systems, mobile computing, strategic planning, and systems acquisition and development. A new chapter on AI and automation clarifies machine learning, artificial intelligence, and natural language processing.